if m=3-√5; prove m²-5m+√5+1=0
Answers
Answered by
5
Given that :
![m = 3 - \sqrt{5} m = 3 - \sqrt{5}](https://tex.z-dn.net/?f=m+%3D+3+-+%5Csqrt%7B5%7D+)
No, we have to prove that :
![{m}^{2} - 5m + \sqrt{5} + 1 = 0 {m}^{2} - 5m + \sqrt{5} + 1 = 0](https://tex.z-dn.net/?f=+%7Bm%7D%5E%7B2%7D+-+5m+%2B+%5Csqrt%7B5%7D+%2B+1+%3D+0)
On taking LHS :
No, we have to prove that :
On taking LHS :
Answered by
1
Answer:
click on the attachment
Step-by-step explanation:
please select my answer as BRAINLIST
Attachments:
![](https://hi-static.z-dn.net/files/d81/7168f211a3faa1abfd97b375f4fc7463.jpg)
Similar questions